Shoe-surface tribology in hardcourt tennis - Hale, J.; Lewis, R.; Carré, M. J. (Proceedings, 2020)
Sports shoes used for hardcourt tennis vary greatly in outsole tread design. In this study, a series of experiments were conducted on individual shoe tread elements, replicating the tribological conditions they will experience during hardcourt step and slide movements. It was found that tread element orientation does not influence the friction during step movements, but has a moderate effect on the friction during hardcourt slides. This is considered to be due to differing amounts of wear and frictional heat experienced.